2007
DOI: 10.1073/pnas.0610124104
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of strong population differentiation shape extended haplotypes across the human CD28 , CTLA4 , and ICOS costimulatory genes

Abstract: The three members of the costimulatory receptor family, CD28, CTLA-4, and ICOS, have complementary effects on T cell activation, and their balance controls the overall outcome of immune and autoimmune responses. They are encoded in a short genomic interval, and overall activity may result from interplay between allelic variants at each locus. With multiethnic DNA panels that represent a wide spectrum of human populations, we demonstrate long-range linkage disequilibrium among the three genes. A large fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
4
27
0
1
Order By: Relevance
“…Our finding of LD between markers in the CTLA4-ICOSe1 and ICOSe2-5 haploblocks supports this. The structure and frequency of haplotypes in the current study are also in accordance with those in the European populations studied by Butty et al 27 The haplotype identified as most common in those European populations is part of our CTLA4-ICOSe1 risk haplotype group 2. Both our risk haplotype groups 2 and 4 carry the allele most commonly associated with CD, rs231775*A (CTLA4 þ 49*A) (Table 5a).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of LD between markers in the CTLA4-ICOSe1 and ICOSe2-5 haploblocks supports this. The structure and frequency of haplotypes in the current study are also in accordance with those in the European populations studied by Butty et al 27 The haplotype identified as most common in those European populations is part of our CTLA4-ICOSe1 risk haplotype group 2. Both our risk haplotype groups 2 and 4 carry the allele most commonly associated with CD, rs231775*A (CTLA4 þ 49*A) (Table 5a).…”
Section: Discussionsupporting
confidence: 91%
“…25,29 A recent study by Butty et al 27 of LD patterns and haplotypes in the CD28-CTLA4-ICOS gene region in a number of populations revealed extended haplotypes covering the whole region. Our finding of LD between markers in the CTLA4-ICOSe1 and ICOSe2-5 haploblocks supports this.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The three members of the costimulatory receptor family, CD28, CTLA4, and ICOS, encoded in a short genomic interval, have complementary effects on T-cell activation and their balance has been shown to control the overall outcome of immune responses. 35 Butty et al 35 have shown that functional variation in the CD28/CTLA4/ICOS region may not be due to polymorphism in a single gene, but to the combination of genetic variants at the three loci. Thus, SNPs in other costimulatory receptors may also be associated with DCM and should be systematically investigated in future studies.…”
Section: Ctla4 Receptor In the Pathogenesis Of Dcmmentioning
confidence: 99%
“…CTLA-4, a receptor structurally homologous to CD28, acts as a negative regulator of T cell responses by interacting with B7 molecules on antigen presenting cells; in contrast, a costimulatory signal is evoked by CD28-B7 interaction (Ling et al 2001, Butty et al 2007). Antibody-mediated blockage of CTLA-4 in vivo has been demonstrated to upregulate the immune response in murine models of infection, autoimmune disease, tumour immunity, allergy and vaccination , Thio et al 2004).…”
mentioning
confidence: 99%